Large‐scale coral reef rehabilitation after blast fishing in Indonesia. Issue 2 (23rd September 2018) - Williams, Susan L.; Sur, Christine; Janetski, Noel; Hollarsmith, Jordan A.; Rapi, Saipul; Barron, Luke; Heatwole, Siobhan J.; Yusuf, Andi M.; Yusuf, Syafyudin; Jompa, Jamaluddin; Mars, Frank
Abstract : The severely degraded condition of many coral reefs worldwide calls for active interventions to rehabilitate their physical and biological structure and function, in addition to effective management of fisheries and no‐take reserves. Rehabilitation efforts to stabilize reef substratum sufficiently to support coral growth have been limited in size. We documented a large coral reef rehabilitation in Indonesia aiming to restore ecosystem functions by increasing live coral cover on a reef severely damaged by blast fishing and coral mining. The project deployed small, modular, open structures to stabilize rubble and to support transplanted coral fragments. Between 2013 to 2015, approximately 11, 000 structures covering 7, 000 m 2 were deployed over 2 ha of a reef at a cost of US174, 000. Live coral cover on the structures increased from less than 10% initially to greater than 60% depending on depth, deployment date and location, and disturbances. The mean live coral cover in the rehabilitation area in October 2017 was higher than reported for reefs in many other areas in the Coral Triangle, including marine protected areas, but lower than in the no‐take reference reef. At least 42 coral species were observed growing on the structures. Surprisingly, during the massive coral bleaching in other regions during the 2014–2016 El Niño–Southern Oscillation event, bleaching in the rehabilitation area was less than 5% cover despite warm water (≥30°C). This project demonstrates that coral rehabilitation is achievable over large scales where coral reefs have been severely damaged and are under continuous anthropogenic disturbances in warming waters.